2018
DOI: 10.1371/journal.pone.0204129
|View full text |Cite
|
Sign up to set email alerts
|

Calving duration and obstetric assistance influence pulmonary function of Holstein calves during immediate fetal-to-neonatal transition

Abstract: Neonatal immediate adaptation to extrauterine life depends mainly on adequate lung function, which is under the influence of previous fetal maturation and obstetrical condition, both acting to stimulate the efficient liquid removal from the pulmonary parenchyma during the immediate transition period. The objective of the present study is to identify chest radiographic changes of neonatal calves born under the influence of different duration of calving and obstetric assistance and correlate with clinical analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…As described in detail previously, using the same study population (Vannucchi et al, 2017(Vannucchi et al, , 2018, we conducted a prospective and observational study in a single dairy herd with high-milk-producing Holstein cows and heifers of BCS between 2.5 and 3.5. The local air temperature and humidity ranged from 17.6 to 23.5°C and from 68.3 to 79.7%, respectively, with an average wind speed ranging from 9 to 11 km/h.…”
Section: Animals and Experimental Groupsmentioning
confidence: 99%
“…As described in detail previously, using the same study population (Vannucchi et al, 2017(Vannucchi et al, , 2018, we conducted a prospective and observational study in a single dairy herd with high-milk-producing Holstein cows and heifers of BCS between 2.5 and 3.5. The local air temperature and humidity ranged from 17.6 to 23.5°C and from 68.3 to 79.7%, respectively, with an average wind speed ranging from 9 to 11 km/h.…”
Section: Animals and Experimental Groupsmentioning
confidence: 99%
“…Longer duration of calving birth increases the risk of maternal and fetal complications and mortality of the newborns. Adaptation of calves to postnatal life depends mainly on lung function, which is affected by fetal development, that stimulates effective removal of fluid from their parenchyma during the transition period (Vannucchi et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…A close correlation could be found between the duration of the second stage of calving and the duration of obstetrical assistance because the prevalence of severely acidotic calves (pH < 7.0) can be increased if the duration of the second stage of calving is extended (<2 h: 0%, 2 to 4 h: 19%, 4 to 7 h: 44%: [ 15 ]). In contrast, besides respiratory acidosis, Vannouchi et al [ 34 ] reported normal mean metabolic parameters (BE: −5.4 mmol/L, HCO 3 − : 20.5 mmol/L, TCO 2 : 21.9 mmol/L) even if the duration of calving was longer than >4 h. At the same time, a significant respiratory depression (altered lung gas exchange and delayed lung clearance) was also observed [ 43 ]. Therefore, it is important to emphasize for the dairy practice that, in agreement with Comline and Siver [ 22 ], not only the pH value and the blood gases but the other acid-base variables will start to move in the direction of expressed respiratory and metabolic acidosis only after appearing the amniotic sac and fetal feet in the vulva during the second stage of labor.…”
Section: Discussionmentioning
confidence: 99%